Theoretical investigations of the chemical bonding in MM'O2 clusters (M, M' = Be, Mg, Ca) - Ponec, Robert; Cooper, David L (Journal of molecular modeling, 2018)
Motivated by the known stability of the somewhat unusual Be2O2 rhombus, which features a short Be-Be distance but no direct metal-metal bonding, we investigate the nature of the bonding interactions in the analogous clusters MM'O2 (M, M' = Be, Mg, Ca). CCSD/cc-pVTZ and CCSD(T)/cc-pVQZ calculations, amongst others, are used to determine optimized geometries and the dissociation energies for splitting the MM'O2 clusters into metal oxide monomers. The primary tools used to investigate the chemical bonding are the analysis of domain-averaged Fermi holes, including the generation of localized natural orbitals, and the calculation of appropriate two- and three-center bond indices. Insights emerging from these various analyses concur with earlier studies of M2O2 rhombic clusters in that direct metal-metal bonding was not observed in the MM'O2 rings whereas weak three-center (3c) bonding was detected in the MOM' moieties. In general terms, these mixed MM'O2 clusters exhibit features that are intermediate between those of M2O2 and M'2O2, and the differences between the M and M' atoms appear to have little impact on the overall degree of 3c MOM' bonding. Graphical abstract Bonding situation in MM'O2 clusters (M, M' = Be, Mg, Ca).
Keywords: Short metal–metal distances without direct bonding; MM′O2 rings; Domain-averaged Fermi hole analysis; Localized natural orbitals; Multicenter bond indices